GAME DESIGN FOR INTERACTIVE COMMUNICATION AT ADVERTISING EVENTS OF UNIVERSITY - Strode, Aina; Loktionova, Viktorija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The aim of the article - to study the essence of game design and the possibilities of usage games in the pedagogical-psychological context, to justify the choice of the game as tool of university advertising. Research methods - theoretical - research of literature and internet resources; empirical - interviews of experts. Since the aim of the projected game is to test and supplement the knowledge about Rezekne Academy of Technologies (RTA) and create interest in studying at RTA, the degree of research of the topic has been done by analyzing publications about the place of game in advertising, as a educational tool, as well as scientific articles about game design, its development process. The concept of advertising game includes the substantiation of the content, organizational, constructive and graphical solution.